Long Term Monitoring of Sleep Disordered Breathing Using IOT Enabled Polymer Sensor Embedded Fabrics - R.S. , Sabeenian; K.R. , Kavitha; E. , Ajay Kishore; S. , Praveen; A.B. , Harshavardhan (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents the design and implementation of health monitoring fabrics incorporated with a wireless biomedical parameter monitoring system supported by different biomedical sensors and the microcontroller unit Arduino UNO with Wi-Fi. The devices can be able to measure physiological parameters like vital signs, heartbeats, and the temperature of a patient who wears the fabrics. The patient is continuously monitored both on the transmitter side and receiver side by the doctor. There are a number of techniques available for the ICU patient’s health monitoring system with wired communication technology. Within the novel system, the patient's health is continuously monitored using wireless sensor networks, and therefore the acquired data is transmitted to a microcontroller unit, Arduino UNO then to Wi-Fi. At the receiver side the information is collected with Wi-Fi and Arduino and displayed on relevant displays.